2007
DOI: 10.1111/j.1751-9004.2007.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Higher Education on Egalitarian Attitudes and Values: Contextual and Cultural Determinants

Abstract: In the present paper, we revisit the question of the impact of higher education on students' egalitarian attitudes and values. Research in this domain indicates that students tend to become more egalitarian and tolerant with higher education, but there are also differences depending on academic disciplines. Two main hypotheses aiming to explain why students' egalitarian attitudes differ as a function of academic disciplines are discussed: self-selection and socialization. Previous research yielding results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…Moreover, inter-parental differences in education did not vary between the latter two groups as we expected. Taking also into account the significant findings on parents’ incomes (Hypotheses 2.1b and 2.2b), our findings may suggest that, at least in our sample, education levels tapped more into parents’ previous exposures to democratic ideals and female role models (and thus endorsement of egalitarian gender role attitudes; Chatard & Selimbegovic, 2007) than into socioeconomic power. In fact, many immigrants report experiencing a significant loss of capacity to translate the education levels achieved in their home country into earning ability in the US (García Coll et al, 1996), meaning that a better educational background may not be able to give them more leverage in negotiating for a more self-favoring division of household labor.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Moreover, inter-parental differences in education did not vary between the latter two groups as we expected. Taking also into account the significant findings on parents’ incomes (Hypotheses 2.1b and 2.2b), our findings may suggest that, at least in our sample, education levels tapped more into parents’ previous exposures to democratic ideals and female role models (and thus endorsement of egalitarian gender role attitudes; Chatard & Selimbegovic, 2007) than into socioeconomic power. In fact, many immigrants report experiencing a significant loss of capacity to translate the education levels achieved in their home country into earning ability in the US (García Coll et al, 1996), meaning that a better educational background may not be able to give them more leverage in negotiating for a more self-favoring division of household labor.…”
Section: Discussionmentioning
confidence: 67%
“…Several studies based on European American (e.g., Blair & Lichter, 1991; Ishii-Kuntz & Coltrane, 1992) and Mexican American (Coltrane & Valdez, 1993; Pinto & Coltrane, 2009) families in the US found that couples had a more balanced division of housework when the wives were more educated and had higher incomes. Modern educational systems expose students to democratic ideals and female role models, and not surprisingly, more educated individuals have more egalitarian attitudes about marital roles (see Chatard & Selimbegovic, 2007 for a review of related studies conducted with samples from both individualistic and collectivistic countries). Higher education also leads to better paying jobs.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation however with our study is of course that we only study the educational effects of one semester. On the other hand, our results show that education in economics, law and political science have various effects after only one semester, and if we think of these effects in terms of socialization, they would potentially increase over time (see discussion in Chatard and Selimbegovic 2007).…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, the college peer group is seen as an important reference group by which students not only seek out shared values in their chosen disciplines and the on-campus experiences they elect to participate in, but one in which they also modify their attitudes, conforming to the norm of the peer group (Guimond, 1997;Renn & Arnold, 2003). Utilizing this socialization hypothesis, one might argue that students become more congruent with the norm of their peer group or academic discipline over the college years because of the conformity to social norms within each reference group (Chatard & Selimbegovic, 2007). Additionally, an informational influence may occur when students receive newly acquired knowledge through their course content or other college experiences.…”
Section: The Impact Of College On Attitudesmentioning
confidence: 96%
“…Furthermore, the wealth of scholarship devoted to understanding the impact of college (Astin, 1993;Pascarella & Terenzini, 2005) points to the association of many educational experiences with less restrictive views (Janus, 2010). College campuses also serve as an influential context that must be accounted for because peer group norms (Chatard & Selimbegovic, 2007) and institutional structures (Pascarella & Terenzini, 2005) contribute to the environment of a student's formative years. Drawing from the theoretical underpinnings and previous empirical research, this study seeks to address the following research questions:…”
Section: Theoretical Frameworkmentioning
confidence: 98%